Astrocyte and Microvascular Imaging in Awake Animals Using Two‐Photon Microscopy. (April 2015) - Tran, Cam Ha T.; Gordon, Grant R.
Abstract Neurovascular coupling is an important control mechanism in CBF regulation. New insights into the integrated relationship between synaptic activity, astrocytes Ca2+, and cerebral blood vessels using two‐photon fluorescence imaging are slowly emerging. Here, we provide a brief overview of the current understandings and controversies regarding astrocytes in activity‐dependent vasodilation. We highlight the key advantages and disadvantages of the in vitro and in vivo methodologies used to study this topic. In particular, we emphasize some of the drawbacks of acute brain slices as well as the confounding effects of anesthesia in in vivo preparations. To overcome these limitations, we discuss an emerging and important trend in imaging cell Ca2+ and blood flow control in awake and behaving animals. This new approach may help resolve existing controversies on astrocyte control of arteriole diameter by providing a more physiologically relevant preparation to study CBF regulation.